A minireview of CYP2C9 AND CYP2C19 Single Nucleotide Polymorphisms (SNPs) among Malaysian populations - Rusli, Ismail; Rosdi, R.A.; Mohd Yusoff, N.; Tan, C.S.; Musa, N.; Yusoff, S. (2017)
It has been recognized extensively that studies of pharmacogenetics provide massive examples of causal relationship between genotypes and drug effectiveness to account for interindividual phenotypic variations in drug therapy. In most cases, cytochrome P450 (CYP) polymorphisms are one of the major variables that affecting those drug plasma concentration, drug detoxification and drug activation in humans. Thus, understanding of CYP polymorphisms can be crucially valuable in order to allow early and more accurate drug dosage prediction and improve the drug response accordingly. Despite the high level of homologous amino acid sequences, CYP2C9 and CYP2C19 genes are among the most important CYP genes which metabolize a wide range of clinically therapeutic drugs. Several critical reviews have been published relating to the aforementioned genes. However, this minireview aims to systematically merge reported studies on the SNPs frequencies of both genes concentrating only on Malaysian population. It is hoped that, the minireview can be an opener for new opportunities to reevaluate the evidence on the prevalence of CYP2C genes as a potential genetic factor influencing a particular drug efficacy and safety among Malaysian. Such evaluation can be developed to the next level of early prediction of better and specific drug treatment, thereby improving the drug response while helping the government in minimising the drug expenditures.